2022
DOI: 10.1038/s41598-022-07925-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of freezing and heating conditions on grape seed flavan-3-ol extractability, oxidation, and galloylation pattern

Abstract: In cool-climate viticulture, the short growing season can influence grape seed maturation by reducing the apparent oxidation of flavan-3-ol monomers and associated increase in seed browning. A reduction in seed maturation increases the potential extraction of flavan-3-ol monomers into wine during maceration operations, heightening bitterness. Here, we carried out a 2 × 2 factorial experiment to test the ability of freezing and heating treatments to advance maturation (decrease flavan-3-ol, improve browning) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Meanwhile, black grape seed extract is one of the supplements that has flavonoid compounds with very high antioxidant effects. The biological properties of polyphenols include antioxidant, anti-cancer, and antiinflammatory effects, among which proanthocyanidin is the most effective anti-oxidant compound of grape seed (15). Zarei et al in 2022 showed the positive and synergistic effects of co-administration of grape seed and regular exercise for 14 weeks to prevent acute and chronic cardiac protective phenomena in heart ischemia rat models (16).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, black grape seed extract is one of the supplements that has flavonoid compounds with very high antioxidant effects. The biological properties of polyphenols include antioxidant, anti-cancer, and antiinflammatory effects, among which proanthocyanidin is the most effective anti-oxidant compound of grape seed (15). Zarei et al in 2022 showed the positive and synergistic effects of co-administration of grape seed and regular exercise for 14 weeks to prevent acute and chronic cardiac protective phenomena in heart ischemia rat models (16).…”
Section: Introductionmentioning
confidence: 99%